Conformational Preference of Potassium Salts of N-Acylhydrazinecarbodithioates with Antifungal Activity. Combined Experimental and Theoretical Approach - Siwek, Agata; Plech, Tomasz; Trotsko, Nazar; Kosikowska, Urszula; Malm, Anna; Dzitko, Katarzyna; Paneth, Piotr (Current Computer - Aided Drug Design, 2014)
In vitro antifungal potency of a set of potassium N-acylhydrazinecarbodithioates was tested. Some of the studied salts displayed significant antifungal activity against Candida spp. at non-toxic concentration indicating a high selectivity of their anticandidal activity. In further study, on the example of conformational analysis, we have tested several force fields and semiempirical parametrizations in order to identify those that could be effectively used for modeling of this class of compounds.
Keywords: Antifungal activity